Method for determining state of slurry by using graded centrifugation

Through the staging centrifugal measurement method, the state of the catalyst slurry is analyzed, and the problem of difficulty in accurately analyzing the state of the catalyst slurry in the prior art is solved, and the detailed analysis of the slurry composition and state is realized, and the forming quality and microstructure of the fuel cell catalytic layer are improved.

CN119715271AActive Publication Date: 2025-03-28SHANGHAI JIAOTONG UNIV +1

Patent Information

Application Number
CN202411655515.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-28
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

The prior art is difficult to accurately analyze the state of the catalyst slurry, mainly because the slurry is a black suspended particle system, with low light transmittance, and a thermodynamic unstable system, and the state is prone to change with the preparation time.

Method used

The slurry state is measured by using staging centrifugation. By centrifuging the slurry to be tested at different rotation speeds, the supernatant is taken and its viscosity, conductivity and light transmittance are measured, and the particle size, stability, resin adhesion state and particle form in the slurry are analyzed.

Benefits of technology

The precise analysis of the slurry state is achieved, and the solid content size distribution of different slurries, the adhesion state between resin and catalyst, the dissociation state and stable state of resin are able to transversely compare, and the problem is difficult to analyze in traditional methods. It is simple to operate and has strong practicality.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a method for measuring the state of slurry by using graded centrifugation. The method comprises the following steps: S1, centrifuging slurry to be measured at different rotating speeds respectively, and taking supernate of the slurry; s2, measuring the viscosity, the conductivity and the light transmittance of the supernate; s3, comparing the viscosity data at different rotating speeds to obtain particle size and stability data of particles in the slurry; comparing the conductivity data at different rotating speeds to obtain adhesion data of ion resin on carbon particles in the slurry; according to the method, the constraint of traditional thinking is broken through, the state of the slurry is analyzed by adopting a method for determining the state of the slurry through graded centrifugation, the problem that the state of the catalyst slurry is difficult to analyze for a long time is solved, and the method is suitable for large-scale popularization and application. The operation method is simple and high in practicability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cells, and in particular to a method for measuring a slurry state by utilizing graded centrifugation. Background Art

[0002] Proton exchange membrane fuel cell is a power generation device that uses hydrogen as fuel and can effectively convert its chemical energy into electrical energy. Its high energy density, fast startup speed, low operating temperature, and environmental friendliness make it very suitable as a power source for electric vehicles, portable small power sources, and underwater power system power sources.

[0003] The state of catalyst slurry is a key factor in determining the performance of the fuel cell catalyst layer. It is composed of catalyst, solvent, ion resin solution and certain additives. By controlling the state of slurry, the molding quality and microstructure of the catalyst layer can be adjusted, thereby improving the battery performance.

[0004] The analysis of the slurry state is the basis for improving the performance of the slurry, but due to the characteristics of the slurry, the analysis work is relatively difficult. First, the slurry is a black suspended particle system. Because of its extremely low light transmittance, most optical analysis methods cannot accurately identify it. Secondly, the slurry is a mixture containing liquid, polymer, and solid particles. The functional groups are complex and there are many interfering factors. It is difficult to use traditional chemical methods to systematically analyze it. Third, the slurry is a thermodynamically unstable system, and its state will change with the preparation time. Fourth, the solid particles in the slurry are all extremely fine particles and mesoscopic colloidal particles, and it is difficult to observe their state by simple methods. At present, in addition to macroscopic viscosity and rheological characteristics tests, the research on slurry will also dilute the slurry and use dynamic light scattering to study its particle size, but the change in slurry state caused by dilution is also inevitable. Summary of the invention

[0005] In view of the defects in the prior art, the object of the present invention is to provide a method for measuring the state of slurry by using fractional centrifugation.

[0006] According to the present invention, a method for determining the state of slurry by using graded centrifugation comprises the following steps:

[0007] S1: The slurry to be tested is centrifuged at different speeds and the supernatant of the slurry is taken;

[0008] S2: measuring the viscosity, conductivity and transmittance of the supernatant;

[0009] S3: Compare the viscosity data at different rotation speeds to obtain the particle size and stability data in the slurry; compare the conductivity data at different rotation speeds to obtain the attachment data of the ion resin on the carbon particles in the slurry; compare the transmittance data at different rotation speeds to obtain the particle form data of the solid particles in the slurry.

[0010] Preferably, the rotation speed ranges from 0 to 10,000 rpm.

[0011] Preferably, the variation base of the different rotation speeds is 1000 revolutions per second.

[0012] Preferably, the rotational speed is represented by R, and the viscosity data at different rotational speeds are compared to obtain the particle size and stability data in the slurry, specifically: when the rotational speed is 0≤R≤5000 rpm, there is a sudden drop in viscosity, there are many large-size particles in the slurry, and the stability is low; when the rotational speed is 5000<R≤10000 rpm, there is a sudden drop in viscosity, there are many small-size particles in the slurry, and the stability is high; there is no sudden drop in viscosity, and the particle size distribution range of the slurry is wide.

[0013] Preferably, the slurry includes carbon particles and resin, wherein the carbon particles are large particles of varying sizes and are easy to settle, and the resin is a conductive polymer that can be ionized and is not easy to settle;

[0014] By comparing the conductivity data at different rotation speeds, the adhesion data of the resin on the carbon particles in the slurry are obtained. Specifically, when the conductivity changes little, the resin dispersion ability is strong, and the resin adhesion on the carbon particles is small, then the resin is not easy to leave the dispersion system as the carbon particles settle; when the viscosity drops suddenly, the conductivity drops suddenly, then the surface resin dispersion ability is weak, and the resin adhesion on the carbon particles is large.

[0015] Preferably, by comparing the transmittance data at different rotation speeds, the particle form data of the solid particles in the slurry can be obtained, specifically:

[0016] The less the resin adheres to the carbon particles, the less likely it is for the resin to leave the dispersion system as the carbon particles settle. The dispersion system has a stronger ability to disperse the resin. The more carbon particles settle, the higher the transparency.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The present invention breaks through the constraints of traditional thinking and realizes the analysis of the slurry state by adopting the method of graded centrifugation to determine the slurry state. The slurry components in different states can be obtained through graded centrifugation. Through testing, the solid content size distribution of different slurries can be compared horizontally, the adhesion state of resin and catalyst of different slurries can be compared horizontally, the resin dissociation state of different slurries can be compared horizontally, the stable state of different slurries can be compared horizontally, the surface energy of the system can be compared horizontally, etc., which solves the long-standing problem of difficulty in analyzing the catalyst slurry state. The operation method is simple and practical. DETAILED DESCRIPTION

[0019] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several changes and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0020] Basic Example:

[0021] The present invention provides a method for determining the state of slurry by using graded centrifugation, comprising the following steps:

[0022] S1: The slurry to be tested is centrifuged at different speeds and the supernatant of the slurry is taken, wherein the speed range is 0 to 10000 rpm, and the variation base of different speeds is 1000 rpm;

[0023] S2: measuring the viscosity, conductivity and transmittance of the supernatant;

[0024] S3: Compare the viscosity data at different rotation speeds to obtain the particle size and stability data in the slurry; compare the conductivity data at different rotation speeds to obtain the attachment data of the ion resin on the carbon particles in the slurry; compare the transmittance data at different rotation speeds to obtain the particle form data of the solid particles in the slurry.

[0025] Since large particles will settle at low speeds and small particles will settle at high speeds, if there are only one size of particles in the slurry, then when a certain speed is reached, all particles will settle together, and the viscosity will suddenly decrease. If there are particles of multiple sizes in the slurry, then each time a speed is reached, a part of the particles will settle, that is, the particles will gradually settle from large to small, so the viscosity will gradually decrease. Specifically, the viscosity data at different speeds are compared to obtain the particle size and stability data in the slurry, specifically: when the speed is between 0 and 5000 rpm, there is a sudden drop in viscosity, there are many large-size particles in the slurry, and the stability is low; when the speed is greater than 5000 rpm and less than 10000 rpm, there is a sudden drop in viscosity, there are many small-size particles in the slurry, and the stability is high; there is no sudden drop in viscosity, and the particle size distribution range of the surface slurry is wide.

[0026] There are two kinds of materials in the slurry of the present invention: carbon particles and resin. Carbon particles are large particles of different sizes and are easy to settle; resin is a conductive polymer, similar to sulfuric acid, which can be ionized but not easy to settle. Carbon particles are dispersed in the slurry, and the resin will appear in two states, one is directly dispersed in the slurry, and the other is attached to the surface of carbon particles. The conductivity of the slurry mainly depends on the resin dispersed in the slurry. These resins are not only ionized but also can move freely. The resin attached to the carbon surface will be restricted in movement and will not affect the conductivity. The viscosity of the slurry is affected by both the resin and the carbon particles, but the concentration of the carbon particles is a decisive factor. Specifically, by comparing the conductivity data at different rotation speeds, the attachment data of the ionic resin on the carbon particles in the slurry can be obtained, specifically:

[0027] A small change in conductivity indicates that the ion resin has a strong dispersibility and less adhesion to the carbon particles, and it is not easy to leave the dispersion system as the carbon particles settle. If the conductivity drops suddenly when the viscosity drops suddenly, it means that the ion resin has a weak dispersibility and the resin is more attached to the carbon particles.

[0028] Furthermore, by comparing the transmittance data at different rotation speeds, the particle form data of the solid particles in the slurry can be obtained, specifically:

[0029] The less the resin adheres to the carbon particles, the more difficult it is for the resin to leave the dispersion system as the carbon particles settle, and the dispersion system has a stronger ability to disperse the resin. Since the resin is transparent, the carbon particles will block light. The more carbon particles settle, the higher the transparency.

[0030] Embodiment 1:

[0031] Take a certain type of slurry, the components of which are: 2g of platinum-carbon catalyst 1, 5g of resin solution 1, 60g of a mixed solution of alcohol 1 (isopropanol): alcohol 2 (n-propanol): triol (propylene glycol): water (1:0.5:0.1:2) (mass ratio), and measure its viscosity, conductivity and transmittance.

[0032] Specifically, the slurry was centrifuged at rotation speeds of 0 rpm, 2000 rpm, 5000 rpm, 8000 rpm, and 10000 rpm, respectively. The supernatant of the slurry after centrifugation was taken to measure its viscosity, conductivity, and transmittance. The measured data are shown in Table 1.

[0033] Table 1: Experimental data after slurry centrifugation in Example 1

[0034] Example 1 <![CDATA[Viscosity( mPa·s) > <![CDATA[Conductivity ( μS / cm)]]> Transmittance(%) 0 75 70 0 2000 31 62 0 5000 20 60 50 8000 11 47 60 10000 4 42 65

[0035] In this embodiment, the viscosity suddenly dropped at a rotation speed of 2000 rpm, indicating that the particle size of the dispersed system of the slurry was larger, D=0.786 μm, and it was easy to settle and had low stability.

[0036] The conductivity of the slurry in this embodiment changes little, which can be inferred that the ionic resin in this embodiment is less attached to the carbon particles and is difficult to leave the dispersion system as the carbon particles settle, and the dispersion system has a stronger dispersion ability for the resin. The conductivity of this embodiment is higher, indicating that the degree of dissociation of the resin is higher. The characterization of the state of the ionic resin on the carbon surface is a classic problem in the industry, and the present invention can infer the adsorption state of the resin from the side.

[0037] The slurry in this embodiment has a high light transmittance, which indicates that the solid particles in the slurry are mainly present in the form of large particles and are easy to settle.

[0038] Embodiment 2:

[0039] Take a certain type of slurry, the components of which are 2g of platinum-carbon catalyst 2, 5g of resin solution 1, and 60g of a mixed solution of alcohol 1 (isopropanol): alcohol 2 (n-propanol): triol (propylene glycol): water (1:0.5:0.1:2) (mass ratio), and measure its viscosity, conductivity and transmittance.

[0040] Specifically, the slurry was centrifuged at rotation speeds of 0 rpm, 2000 rpm, 5000 rpm, 8000 rpm, and 10000 rpm, respectively. The supernatant of the slurry after centrifugation was taken to measure its viscosity, conductivity, and transmittance. The measured data are shown in Table 2.

[0041] Table 2: Experimental data after slurry centrifugation in Example 2

[0042] Example 2 Viscosity (mPa·s) Conductivity (μS / cm) Transmittance(%) 0 52 15 0 2000 47 12 0 5000 42 13 10 8000 23 12 31 10000 6 11 42

[0043] In this embodiment, the viscosity suddenly dropped at a rotation speed of 8000 rpm, indicating that the particle size of the dispersed system of the slurry is smaller, D=0.235 μm, is not easy to settle, and has high stability.

[0044] The conductivity of the slurry in this embodiment changes little, indicating that the ionic resin in this embodiment is less attached to the carbon particles and is difficult to leave the dispersion system as the carbon particles settle, and the dispersion system has a stronger dispersion ability for the resin. The conductivity of this embodiment is lower, indicating that the degree of dissociation of the resin is lower.

[0045] The light transmittance of the slurry in this embodiment is relatively low, indicating that the solid particles are highly dispersed in the slurry in the form of small particles and are difficult to settle.

[0046] Embodiment 3:

[0047] Take a certain type of slurry, the components of which are 2g of platinum-carbon catalyst 3, 5g of resin solution 2, and 60g of a mixed solution of alcohol 1 (isopropanol): alcohol 2 (n-propanol): triol (propylene glycol): water (1:0.5:0.1:2) (mass ratio), and measure its viscosity, conductivity and transmittance.

[0048] Specifically, the slurry was centrifuged at rotation speeds of 0 rpm, 2000 rpm, 5000 rpm, 8000 rpm, and 10000 rpm, respectively. The supernatant of the slurry after centrifugation was taken to measure its viscosity, conductivity, and transmittance. The measured data are shown in Table 3.

[0049] Table 3: Experimental data after slurry centrifugation in Example 3

[0050] Example 3 Viscosity (mPa·s) Conductivity (μS / cm) Transmittance(%) 0 21 55 0 2000 15 42 20 5000 12 41 52 8000 11 31 53 10000 4 24 71

[0051] The viscosity in this embodiment decreases relatively steadily, indicating that the particle distribution range of the slurry in this embodiment is relatively wide, with D being 0.386 μm to 0.521 μm.

[0052] The transmittance of the slurry in this example changes steadily, similar to the viscosity change, indicating that its particle distribution range is relatively wide. At the same time, the final transmittance of the slurry in this example is relatively large, which also indicates that the surface energy of the system is relatively large and the solid particles are not easy to suspend.

[0053] In summary, by comparing the various embodiments, the viscosity of the embodiment 1 and the embodiment 2 dropped suddenly at the rotation speeds of 2000 rpm and 8000 rpm, respectively, indicating that the particle size of the dispersion system of the embodiment 1 is larger, the stability is lower, and it is easy to settle, while the particle size of the dispersion system of the slurry in the embodiment 2 is smaller, the stability is higher, and it is not easy to settle. The viscosity of the embodiment 3 dropped more steadily, indicating that the particle size distribution range of the embodiment 3 is wider.

[0054] Compared with Examples 1 and 3, the conductivity change of Example 2 is smaller, indicating that the ion resin in Example 2 is less attached to the carbon particles and is less likely to leave the dispersion system as the carbon particles settle, and the dispersion system has a stronger dispersion ability for the resin. The resin is transparent, and the carbon particles will block light. The more carbon particles settle, the higher the transparency.

[0055] Compared with Examples 1 and 3, Example 2 has a lower conductivity, indicating that the degree of dissociation of the resin is lower. Example 2 actually uses a resin different from other examples, and the conductivity changes little with the centrifugal speed, indicating that there is less attached resin, and most of the resin does not settle with the carbon particles, and the conductivity can be maintained in a small range. However, although this resin has less attachment, its own dissociation degree is low, resulting in low slurry conductivity.

[0056] Compared with Examples 1 and 3, the transmittance of Example 2 is smaller, indicating that the solid particles are highly dispersed in the slurry in the form of small particles and are difficult to settle. The transmittance of Example 1 changes smoothly, similar to the viscosity change, indicating that there are more large particles and relatively fewer small particles. At the same time, the final transmittance of Example 3 is larger, which also indicates that the surface energy of the system is larger and the solid particles are not easy to suspend.

[0057] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various changes or modifications within the scope of the claims, which does not affect the essence of the present invention. In the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other arbitrarily.

Claims

1. A method for determining the state of a slurry using fractional centrifugation, characterized in that: The steps include: S1: The slurry to be tested is centrifuged at different speeds and the supernatant of the slurry is taken; S2: measuring the viscosity, conductivity and transmittance of the supernatant; S3: Compare the viscosity data at different rotation speeds to obtain the particle size and stability data in the slurry; compare the conductivity data at different rotation speeds to obtain the attachment data of the ion resin on the carbon particles in the slurry; compare the transmittance data at different rotation speeds to obtain the particle form data of the solid particles in the slurry.

2. The method for measuring slurry state by using fractional centrifugation according to claim 1, characterized in that: The rotation speed range is 0 to 10,000 rpm.

3. The method for measuring slurry state by using fractional centrifugation according to claim 1, characterized in that: The base number of the different speed changes is 1000 rpm.

4. The method for measuring slurry state by using fractional centrifugation according to claim 1, characterized in that: The rotation speed is represented by R. The viscosity data at different rotation speeds are compared to obtain the particle size and stability data in the slurry. Specifically, when the rotation speed is within 0≤R≤5000 rpm, the viscosity suddenly drops, and there are many large-size particles in the slurry, and the stability is low; when the rotation speed is within 5000<R≤10000 rpm, the viscosity suddenly drops, and there are many small-size particles in the slurry, and the stability is high. There is no sudden drop in viscosity and the particle size distribution range of the slurry is wide.

5. The method for measuring slurry state by using fractional centrifugation according to claim 1, characterized in that: The slurry includes carbon particles and resin, wherein the carbon particles are large particles and are easy to settle, and the resin is a conductive polymer that can be ionized and is not easy to settle; By comparing the conductivity data at different rotation speeds, the adhesion data of the resin on the carbon particles in the slurry are obtained. Specifically, when the conductivity changes little, the resin dispersion ability is strong, and the resin adhesion on the carbon particles is small, then the resin is not easy to leave the dispersion system as the carbon particles settle; when the viscosity drops suddenly, the conductivity drops suddenly, then the surface resin dispersion ability is weak, and the resin adhesion on the carbon particles is large.

6. The method for measuring slurry state by using fractional centrifugation according to claim 5, characterized in that: By comparing the transmittance data at different rotation speeds, the particle form data of the solid particles in the slurry can be obtained, specifically: The less the resin adheres to the carbon particles, the less likely it is for the resin to leave the dispersion system as the carbon particles settle. The dispersion system has a stronger ability to disperse the resin. The more carbon particles settle, the higher the transparency.

Citation Information

Patent Citations

  • Method for evaluating stability of slurry

    CN101382489A

  • Method for testing stability of cathode slurry and preparation method of cathode slurry

    CN102539294A

  • Evaluation method of stability of lithium-ion battery positive and negative electrode paste

    CN106124363A

  • Lipase visual detection method based on liquid viscosity change and detection kit

    CN114894668A

  • Method and equipment for evaluating stability of battery slurry

    CN114975861A

Cited By

  • Evaluation method for homogenizing effect of lithium ion battery slurry

    CN121721225A

  • Recovery and utilization method of fuel cell catalyst slurry

    CN121885663A